Dulaan a documentary on the Spanish influence on Philippine theater - Cultural Center of the Philippines; Tiongson, Nicanor G.; Del Mundo, Jaime; Marasigan, Dennis N. (Manila The Center, 1992)
This video discusses the various forms of Spanish-influenced theater - from the komedya, the sinakulo, the sarswela to the drama - and how contemporary playwrights and theater groups have revived or innovated them.
VHS.
Narration, Cecilia B. Garrucho ; producers, Rowena E. Concepcion, Mary Ann Ines-Loveria.
Keywords: Theater -- Philippines; Philippine drama -- Spanish influences; Christian drama -- History and criticism. -- Philippines; Theater and society -- Philippines